Immunological Changes on Allergic Response after Beevenom Immunotherapy - Dong-Ha Han (Korean Pharmacopuncture Institute, 2004)
Beevenom immunotherapy(BVIT) in allergic patients is a well-established treatment modality for the prevention of systemic anaphylactic reactions caused by insect stings. BVIT is accompanied by increases in allergen-specific IgG, particularly the IgG4 isotype, which blocks not only IgE-dependent histamine release from basophils but also IgE-mediated antigen presentation to T cells. Inhibition of T cells after BVIT also involves decreased induction of the costimulatory molecule ICOS, which, in turn, seems to be dependent on the presence of IL-10, also associated with the inhibited status of T cells after BVIT. Suppression of T cells by IL-10 is an active process, which depends on the expression and participation of CD28. Immune tolerance in specific allergen immunotherapy might be a consequence of decreased Th2 or increased Th1 response of allergen specific T lymphocytes. BVIT shifted cytokine responses to allergen from a TH-2 to a TH-1 dominant pattern, suggesting direct effects on T cells. Many studies showed that severe side effects due to venom immunotherapy are rare. These results suggest that immunological changes after BVIT may be applied to be therapeutic alternative of general allergic diseases including beevenom allergy.